Stocks and flows of natural capital: Implications for Ecological Footprint. (June 2017) - Mancini, Maria Serena; Galli, Alessandro; Niccolucci, Valentina; Lin, David; Hanscom, Laurel; Wackernagel, Mathis; Bastianoni, Simone; Marchettini, Nadia
Highlights: Footprint's inability to track depletion of natural capital stocks is acknowledged. A comprehensive overview of natural capital's stocks and flows dynamics is provided. A research line is proposed to distinguish stock vs. flow in Ecological Footprint. Abstract: Over the past decade, Ecological Footprint has become one of the most popular and widespread indicators for sustainability assessment and resource management. However, its popularity has been coupled, especially in recent years, by the emergence of critical views on the indicator's rationale, methodology and policy usefulness. Most of these criticisms commonly point to the inability of the Ecological Footprint to track the human-induced depletion of natural capital stocks as one of the main shortcomings of the methodology. Fully addressing this issue will require research efforts and, most likely, further methodological refinements. The aim of this paper is therefore to outline the basis of a new area of investigation in Ecological Footprint research, primarily aimed at implementing the distinction between the use of stocks and the use of flows in Ecological Footprint Accounting and debating its implications.